2016
DOI: 10.1016/j.micinf.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A working model for the type III secretion mechanism in Chlamydia

Abstract: It has been appreciated for almost 20 years that members of the Chlamydiales possess a virulence-associated type III secretion mechanism. Given the obligate intracellular nature of these bacteria, defining exactly how type III secretion functions to promote pathogenesis has been challenging. We present a working model herein that is based on current evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 75 publications
(150 reference statements)
2
23
0
2
Order By: Relevance
“…Sol-mediated suppression of the T3S system has also been reported in enterohemorrhagic Escherichia coli strains (29). The precise details of the T3S process remain unclear in C. trachomatis, but they are developmentally regulated (30)(31)(32), and EBs have the assembled T3S apparatus (33). Our data, indicating that Sol does not prevent EBs from infection, suggest that direct blockage of the T3S apparatus in EBs is unlikely the main mechanism for Sol-induced T3S perturbation.…”
supporting
confidence: 48%
“…Sol-mediated suppression of the T3S system has also been reported in enterohemorrhagic Escherichia coli strains (29). The precise details of the T3S process remain unclear in C. trachomatis, but they are developmentally regulated (30)(31)(32), and EBs have the assembled T3S apparatus (33). Our data, indicating that Sol does not prevent EBs from infection, suggest that direct blockage of the T3S apparatus in EBs is unlikely the main mechanism for Sol-induced T3S perturbation.…”
supporting
confidence: 48%
“…Similarly, a loss of function mutation in the gene ctl0233 ( C. trachomatis L2) that codes for CPAF [46] reduced the L2 organism survival in the mouse lower genital tract [47] while mutations in tc0668 and/or tc0237 significantly attenuated the pathogenicity of the C. muridarum organisms [48, 49]. Studies based on the cell culture system have revealed many chromosomal genes that may play significant roles in chlamydial pathogenesis [5056]. Further animal model evaluations of these gene products in chlamydial pathogenicity may dramatically expand the list of chlamydial virulence factors.…”
Section: The Plasmid Contributes To Chlamydial Pathogenicitymentioning
confidence: 99%
“…Furthermore, we found that 2-amino-phenoxazine-3-one (phenoxazine derivate, Phx-3: a small hydrophobic molecule) induced the destruction of C. pneumoniae in inclusion bodies in immortal epithelial HEp-2 cells, resulting in bacterial growth inhibition [34]. Interestingly, since chlamydial maturation in inclusion bodies is required for manipulation of infected host cells through several effector molecules secreted by type III machinery [35], the dysfunction of type III secretion machinery by the binding of small hydrophobic molecules impaired chlamydia growth in host cells [36]. Although more studies are needed to clarify the mechanisms by which capsaicin causes bacterial morphological changes, it may be that the interaction of small hydrophobic molecules with unknown receptors on the bacterial cell wall is responsible for the dysfunction in bacterial maturation.…”
Section: Discussionmentioning
confidence: 99%